Family and environmental citizenship in a public educational institution in the province of Huancayo, Junín - Benturo Ignacio, Karina (2018)
The research was carried out with the objective of analyzing the role played by the family in the formation of the environmental citizenship of the students from the “17 de Setiembre” School, El Tambo, Huancayo, for which, the scientific and analytical method was used. The research is of a basic type, with a mixed methodological approach, a descriptive level and a nested or embedded design of the dominant model (DIAC, by its acronym in Spanish). Data was collected through two instruments: questionnaire and semi-structured interviews. The questionnaire was applied to a sample of 43 students (from both sexes), 28 women and 15 men who are in the fifth grade of secondary education. Interviews were applied to a mother of family and 2 teachers who teach subjects related to the environment in the same educational institution. The data was processed using the statistical software SPSS V. 21, and for the hypotheses verification, the binomial test statistic of Bernoulli was used with the help of the statistical program Minitab V. 21. For the qualitative information processing, the interviews were transcribed through Microsoft Word. The research concludes that the family, as the first agent of socialization, did not manage to train environmental citizens, since it does not contributed to the formation of rights, responsibilities, values, norms and habits in favor of the environment of its members.   DOI: https://doi.org/10.31876/sl.v2i2.5